Controlled release of niacinamide from fibrous silica nanocarrier in face serum formulation - Nuramira Fateha, Sukor; Rohayu, Jusoh; Nur Syahirah, Kamarudin (Elsevier Ltd, 2023)
The current study offers controlled release of niacinamide from fibrous silica (KCC-1) loaded in a face serum formulation. Furthermore, three drug loading methods, namely physical mixing, melting, and solvent evaporation, denoted as (Phy)/Nia-KCC-1, (Mel)/Nia-KCC-1, and (Sol)/Nia-KCC-1, respectively, were implemented, and the percentage loading efficiencies were compared. (Mel)/Nia-KCC-1 demonstrated the highest percentage of drug loading at 33%, followed by (Phy)/Nia-KCC-1 and (Sol)/Nia-KCC-1 at 25% and 17%, respectively. Likewise, the in vitro release study also revealed a similar pattern, with (Mel)/Nia-KCC-1 recording the highest percentage release at 29%, followed by (Phy)/Nia-KCC-1 and (Sol)/Nia-KCC-1 at 24% and 21%, respectively. As the (Mel)/Nia-KCC-1 sample unveiled decent results in transporting the sample drug, the respective sample was then further loaded into the face serum formulation, and the pH stability was observed for 7 days. The pH readings remained constant at pH 4.3 throughout the 7 days, within the acceptance range according to the derma-cosmetic product that states the effective pH should lie between pH 4 and pH 6. Therefore, it can be stated that the (Mel)/Nia-KCC-1 loaded serum fulfills the acceptance criteria for the pH requirement of derma-cosmetic products.